PROPOSITION D’UNE ÉCHELLE DE MESURE POUR ÉVALUER LA SATISFACTION DU PERSONNEL DES ADMINISTRATIONS PUBLIQUES MAROCAINES - Hanana, Ellarmani Ben; Houfaidi, Souad (European Scientific Journal, ESJ, 2015)
People satisfaction is integrated as well as the customer satisfaction in quality approaches, including total quality. To improve this satisfaction in the Moroccan public administrations and therefore the quality of services provided to users, it is essential that managers and policy makers have at their disposal valid questionnaires to assess the level of satisfaction of their staff and identify the determinants of satisfaction. Our research is part of this perspective and the results allowed us to distinguish three levels of staff satisfaction (61.2%: mid level, 19.7%: high level and 19.1%: low level). It also allowed us to highlight the significant influence of all the dimensions of the proposed scale that the dimension "conditions, work organization and content", alone explains a significant proportion of 53.7% of the variance of the satisfaction overall variable